A REVIEW ON ADAPTIVE FORWARDING IN NAMED DATA NETWORKING - Goyal, Rajeev (International Journal of Engineering Technologies and Management Research, 2018)
Named Data Networking (NDN) is an as of late proposed new Internet architecture. By naming information rather than location, it changes the essential system service abstraction from "transmitting packets to offered destinations" to "retrieving information of given names." This major change makes a plenitude of new opportunities as well the same number of scholarly difficulties in application advancement, system routing and sending correspondence security and protection. In this study, researchers will propose a new architecture of NDN with smart and automated forwarding information based which is more versatile and proficient.